Venice and the radical reformation: Italian anabaptism and antitrinitarianism in European context - Suitner, Riccarda (Refo500 academic studies, 2024)
"The Republic of Venice was the only Catholic territory in which an Anabaptist community formed in the 16th century. The history of Venetian Anabaptism, hitherto little known in Reformation Studies, is the focus of this book. Using a large quantity of archival material and rare printed sources Riccarda Suitner reconstructs the lives of the Republic's Anabaptists and the inquisitorial repression they suffered, and analyses the doctrinal specificities of the Radical Reformation in this area. This story represents a fundamental stage in the relations between German, central-European and Italian culture in the early modern period. Events in Venice are presented within a broader comparative framework, paying particular attention to the German states, Switzerland, the Polish-Lithuanian Commonwealth, Transylvania, Moravia, Tyrol, and the Kingdom of Naples. It will emerge that its Venetian history cannot be ignored if we are to gain a true understanding of the European Reformation." --